THE EFFECTIVENESS OF THINK-PAIR-SHARE METHOD COMBINED WITH PICTURE SERIES TO IMPROVE STUDENTS’ WRITING SKILL - Lulux Nabila Chifa; Santi Andriyani (IKIP Siliwangi, 2024)
Writing is the process to organize and formulate the ideas into a written text. Writing plays a crucial role in language learning. Writing has challenges for many students ; most students find it difficult to express their ideas in writing process. Then, students have little motivation in following the lesson. Therefore, the teachers are anticipated to utilize a teaching mehod that can overcame the problems in writing. This study aimed to find out the effectiveness of Think Pair Share method combined with picture series to improve students’ writing skill for tenth grade at MA Masalikil Huda Tahunan, Jepara. The method used a quasi experimental design with the non-equivalent control group. The data were collected through test in the form of essay test. The population of this study was tenth-grade students at MA Masalikil Huda Tahunan, Jepara. They were two classes namely XIPA as experimental class and XIPS as control class which consisting of 25 students. As a result, the average score of students in experimental was 78.16 whereas in control group was 70.36. The t-test analysis revealed that Sig. (2-tailed) was 0.01 which was less than 0.05. It can be inferred that the use of Think-Pair-Share method combined with picture series was effective towards students’ writing skill.